SMEs and their accessibility to Islamic financing in Malaysia - Abdullah, Moha Asri; Mohd Alwi, Norhayati; Sulaiman, Maliah; Abdul Razak, Dzuljastri; Mohd Thas Thaker, Mohamed Asmy; Ismail, Yusof; Maulan, Suharni (2020)
Small and medium-sized enterprises (SMEs) contributes significantly to the economic and social development of Malaysia. The SME sector provides new job opportunities, stimulates competition and thus boost productivity which are then translated into lower unemployment rate and many other substantial benefits to the economy. Hence, to ensure the sustainability of the SMEs, an understanding towards their financial literacy especially on the accounting practices and financial literacy are worth studying for. This study will provide an indicator on the level of financial literacy of SMEs and on how SMEs have used accounting information to sustain their businesses. The findings of the study will also provide useful information and potential policy remedies to policy makers, researchers and SMEs owners especially in the context of SMEs in the Muslim countries. The survey was conducted using a structured questionnaire that involved 16 questions in terms of a) record keeping, b) budgeting, c) use of accounting information, and d) financial literacy. Data collected from 344 respondents from Klang Valley were analyzed using descriptive statistics.